Orange is the new black: Kinases are the new master regulators of tumor suppression. Issue 6 (11th December 2018) - An, Elvira; Brognard, John
Abstract: For many decades, kinases have predominantly been characterized as oncogenes and drivers of tumorigenesis, because activating mutations in kinases occur in cancer with high frequency. The oncogenic functions of kinases relate to their roles as growth factor receptors and as critical mediators of mitogen‐activated pathways. Indeed, some of the most promising cancer therapeutic agents are kinase inhibitors. However, cancer genomics studies, especially screens that utilize high‐throughput identification of loss‐of‐function somatic mutations, are beginning to shed light on a widespread role for kinases as tumor suppressors. The initial characterization of tumor‐suppressing kinases— in particular members of the protein kinase C (PKC) family, MKK4 of the mitogen‐activated protein kinase kinase family, and DAPK3 of the death‐associated protein kinase family— laid the foundation for bioinformatic approaches that enable the identification of other tumor‐suppressing kinases. In this review, we discuss the important role that kinases play as tumor suppressors, using several examples to illustrate the history of their discovery and highlight the modern approaches that presently aid in the identification of tumor‐suppressing kinases. © 2018 IUBMB Life, 71(6):738–748, 2019